Disciplinary, generic and culture-specific writing conventions: Which matter in English-language academic writing by Russian authors? - Boginskaya, Olga A. (Вестник Томского государственного университета. Филология)
The article deals with insufficiently studied academic prose by Russian writers who have been actively using English in academic settings only for the last fifteen years. To meet the requirements of international academia, Russian scholars need to have a good command of English for performing academic tasks, including publishing their research findings in international journals in order to get promoted in the field. The study has been inspired by the increasing interest in variations in the use of metadiscourse in English academic texts across disciplinary boundaries. Its main focus is on the repertoire and distribution of interactional metadiscourse markers in research article abstracts by nonnative English writers working in social sciences and engineering. In order to investigate metadiscourse in Russian-authored academic writing from a cross-disciplinary perspective, this study adopted a combination of quantitative and qualitative methods. Data collected from 240 research article abstracts was examined for cross-disciplinary differences in the use of metadiscourse. Hyland's taxonomy of interactional metadiscourse was adopted for the analysis. This study aimed to confirm the findings obtained by other researchers who claim that social science authors interact more with the audience than their counterparts in engineering and that differences in the deployment of metadiscourse are more influenced by the disciplinary or generic norms rather than cultural backgrounds of writers. To achieve this aim, the study analyses disciplinary preferences in shaping knowledge through the employment of metadiscourse seeking to identify (1) cross-disciplinary differences in the frequency of occurrence of metadiscourse markers; (2) cross-disciplinary differences in the frequency of the types of hedging, boosting, attitude, self-mention and engagement; (3) cross-disciplinary differences in the use of lexical units that serve metadiscourse functions. The results revealed that while research article abstracts derived from the social science journals included five categories of interactional metadiscourse (hedging, boosting, attitude, engagement, and self-mention), in engineering research article abstracts only four types (hedging, boosting, attitude, and self-mention) appeared. The frequency of occurrences of metadiscourse categories and types also varied across disciplines. The findings confirmed the assumption that metadiscourse is expressed in accordance with the accepted disciplinary and genre-specific norms rather than influenced by cultural backgrounds of L2 writers. Due to a small number of research article abstracts collected to build the corpus, the research results can be interpreted only as trends in the two disciplines. Through a study of interactional preferences of writers from a larger number of disciplines, we will learn more about rhetorical practices and values.